KESETARAAN GENDER DALAM PERSPEKTIF HADIS - junaid, hamzah (PSW, 2012)
This paper examines gender in hadits perspective stating two main topics, namely: what is gender and how the views of hadits about gender. At the same time it also try to give an explanation about the position and role of woman in life that can not be distinguished by men.In order to make the discussion of the gender in hadits perspective can be directed systematically, the above main subject matter is limited in the sub-problems: Is it true that the creation of woman from a crooked rib? It is apparently not enough if it is just understood textually, do men has singularity of worship than woman? Men and woman have singularities for each, can a woman be imam? It is allowed in a certain condition, how is womenâs leadership? Woman are not prevented from being a leader if they have enough potensial to lead, how do woman make partnership with men? Men can partner well with woman.Based on information obtained from hadith, it understood that Allah glorify humanity, both men and woman without distinction except virtue of piety.